Current Status and Future Prospects of Business Technology Research: A Multidimensional Bibliometric Review - Ajouz, Mousa; Abu-AlSondos, Ibrahim (Ahliya Journal of Business Technology and MEAN Economies, 2024)
In the rapidly evolving field of business technology, understanding its current status and prospects is crucial for fostering innovation and achieving competitive advantage. This study aims to dissect business technology research’s intellectual and influential dynamics, offering quantitative insights and a comprehensive review of its literature. Employing a multidimensional bibliometric approach, this research scrutinizes 177 articles published in the Scopus database from 1985 to 2024. Utilizing advanced analytical tools such as RStudio and VOSviewer, the study meticulously analyzes the data, applying sophisticated bibliometric tests to decode the complex dynamics of business technology research. The results highlight the leading journals, authors, and collaborative networks shaping the domain. Notably, the Journal of Information Technology Research emerges as a central hub of scholarly activity. The research delineates several major thematic streams within business technology: Digital Transformation and Industrial Management, Technology Innovation in SMEs, Information Technology and E-Commerce, E-Business Strategies and Profitability, Information Systems and Business Processes, and Supply Chain Management and Social Responsibility. The study also uncovers significant research gaps in the current literature and proposes future research directions, setting a foundation for further empirical exploration. This research represents a pioneering effort in applying a bibliometric approach to business technology. The findings and proposed future research avenues provide both researchers and practitioners with a robust quantitative foundation for understanding the scientific development of business technology, paving the way for further scholarly inquiry and practical application in this vital field.